Bronchial Blocker Provides Hemodynamic stability for One Lung Ventilation in Right Video-Assisted Thoracoscopic Surgery: An Observational Study (Journal of the Bangladesh Society of Anaesthesiologists, 2021)
Background: Double lumen endotracheal tubes (DLT) and bronchial Blockers (BB) have been both beenused for lung isolation in video-assisted thoracic surgery (VATS) with some inherent demerits.Objective: The aim of this study was to observe the quality of lung deflation of a bronchial blocker forone lung ventilation & the hemodynamic stability in video-assisted thoracic surgery(VATS).Materials & methods: A total forty adult patients have been assigned to observe the effects & hemodynamicstability of BB who undergoing VATS procedure for mediastinal mass surgery. Correct placement ofairway was confirmed by fiber optic bronchoscopy. The variables assessed were: 1. Time required forcorrect placement of device, 2. Time taken for lung collapse, 3. Quality of Lung collapse, 4. Number oftimes of airway mal-positioned, 5. Changes of blood pressure and heart rate at baseline (T1) and immediatebefore (T2) and after (T3) intubation and one minute after (T4) intubation, 6. Number of patients withhypoxemia (Spo2